INOVASI PEMBELAJARAN IPAS: PENGGUNAAN MEDIA AUDIOVISUAL PADA MATERI NORMA DALAM ADAT ISTIADAT DAERAHKU DI MI ISLAMIYAH 01 MADIUN - Melik Budiarti; Ratih Indriana Yuliati; Novia Karisma Putri; Ema Fitriana Chayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study addresses the low learning outcomes of fourth-grade students at MI Islamiyah 01 Madiun in the subject of Social Sciences (IPAS), specifically on the topic of